DISTRIBUCION GEOGRAFICA Y RESPUESTA VISUAL DE RHAGOLETIS TOMATIS FOOTE (DIPTERA: TEPHRITIDAE) A TRAMPAS ESFERICAS Y RECTANGULOS DE DIFERENTES COLORES - Frías L., D.; González, C.; Henry, A.; Alviña, A. (Acta Entomológica Chilena, 2022)
Green, yellow and red spherical and rectangular traps were tested to detected Rhagoletis tomatis population. All the traps were covered with stickem and installed in a tomatoes area, II Región of Chile. We studied their eficiency regard to the distance and height in relation with the plants. Some laboratory tests with yellow, red and green spheres 3 cm wide in laboratory cages were also carried out to estímate the number of visits of males and females to spheres. The results indícate that the yellow 10 cm spheres were more efficient than the fíat traps and spheres of other colour and size. The trap efectiveness in field increases considerably when they are located between the tomatoes owns. We concluded that the yellow plástic 10 cm spheres with protein hydrolized in their interior covered with stickem and localized between plants, can detect eficiently adults of R. tomatis. Also, servicing this kind of trap from the first to the seventh región in Chile, revealed captures only in the second región. The presence of R. tomatis is only detected in the Chimba agricultural area and the city of Antofagasta in the second región of Chile.